Pemberdayaan Perempuan Melalui Inovasi Keripik Pisang di Desa Haruyan Dayak Kecamatan Hantakan Kabupaten Hulu Sungai Tengah - Panjaitan, Klara Septari; Budhi, Setia; Suhasti, Indri; Mustaqimah, Wafiq; Aziza, Wafiq; Fatahilah, Muhammad Ibnu; Adnina, Rania; Fatimah, Siti; Sa’diah, Halimatus; Hermawan, Hery; Sembiring, Philips Silwanus Elifiel (Prodi Sosiologi FISIP ULM, 2025)
Haruyan Dayak Village, Hulu Sungai Tengah Regency has abundant natural potential, one of which is bananas. Women play a central role in maintaining stability and economic development in the village. As the main pillar, women have great potential to make a real contribution to the local economy. This service program aims to utilize natural potential into an innovative product that can be marketed at a higher price. The main focus in this research is women's empowerment. The result of this service program is that it is able to improve the economy of women in Haruyan Dayak Village through women's empowerment as well as through training and collaboration so that women can create various variants of banana chips. This innovation not only increases product competitiveness in the market, but also strengthens solidarity among women and social networks that support each other. In this service, the service team applies the live-in method, namely staying at the service location with the aim of building closer interactions with the community and participating in the activities of the Haruyan Dayak Village community. Service activities will be carried out from 18 July 2024 to 13 September 2024, which will be carried out through the initial stages to the final stages so as to produce outputs and outcomes which are the targets of this service. The research results show that banana innovation is able to create new business opportunities, improve women's skills, and make a significant contribution to increasing household income.